Black carbon and other light‐absorbing impurities in snow across Northern China. Issue 3 (11th February 2013) - Wang, Xin; Doherty, Sarah J.; Huang, Jianping
Abstract : [1] Black carbon (BC), organic carbon (OC), and mineral dust (MD) are the most important light‐absorbing particulate impurities in snow. A field campaign was conducted in January and February 2010 to measure light‐absorbing particles in snow across northern China. About 400 snow samples were collected at 46 sites in six provinces. A spectrophotometer was used to separate snow particulate absorption by BC and non‐BC constituents, based on the different spectral dependences of their light absorption. Light absorption by MD is due to iron oxides, so iron concentration was determined by chemical analysis. Using assumed mass absorption efficiencies for BC, OC, and iron, the fractional contribution of each to total absorption was estimated. BC is a product of combustion and iron is associated with MD, but OC in snow can be associated with either combustion products deposited to snow or from soil mixed into snow. The lowest concentrations of BC were in the remote northeast on the border of Siberia, with a median concentration in surface snow of 117 ng g –1 . South of this, in the industrial northeast, the median snow BC concentration was 1220 ng g –1 . In the northeast, snow particulate light absorption was dominated by BC. Across the grassland of Inner Mongolia, OC, likely mostly from local soil, dominates light absorption, with median BC concentrations of 340 ng g –1 responsible for only about one third of total particulate light absorption. In the Qilian Mountains, at the northern boundary of the Tibetan Plateau, snow particulate light absorption is dominated by local soil and desert dust. Key Points: BC, OC, and MD are important light‐absorbing particulate impurities in snow In region 1, snow particulate light absorption is dominated by desert dust The model and measurement show general agreement of black carbon content in snow